An effective way for targeting EGFR-mediated carcinogenesis: an in vitro study - Viktoria A. Pakina; Evgeniya Z. Iksanova; Evgeniya V. Shih; Oksana М. Tumutolova; Karen K. Arutiunian; Irina V. Kargina; Kirill D. Blinov; Fedor P. Pilgaev; Anna A. Epishkina; Dmitrii S. Blinov; Evgeny V. Grebenkin; Ekaterina V. Blinova (Belgorod National Research University, 2024)
Introduction: EGFR-activating overexpression or somatic mutations are common in different human cancers. In this regard, the search for promising ways to control the carcinogenic transformation of tumor cells and the progression of malignant tumors expressing EGFR seems to be one of the most promising and developing areas of modern molecular pathology and pharmacology. Material and Methods: An antitumor activity of a novel compound, a pyridine carboxylic acid derivative LHT-17-19, was studied. The molecule was developed and synthesized at the Department of Chemistry, Drug Design and Technology of All-Russian Research Center for Biological Active Compounds Safety (Russia). The study was carried out in cell cultures of stomach cancer (Hs746T, AGS and MKN1) and patient-derived organoid (PDO) model of breast cancer (BC) expressing wild-type EGFR. Results: It was shown that LHT-17-19 induced concentration-dependent cytotoxicity of EGFR-expressing gastric cancer cells of all the aforementioned cultures. Pathomorphological, immunohistochemical and molecular validation of BC organoids derived from ductal breast carcinoma cells of a 68-year-old patient was done. PDOs were established as ER-negative, PR-negative, Her2/neu-negative, EGFR-positive with 35% of the Ki-67 expression index. In addition, the tumor cells translocation was resulted in a loss of ER expression and PDOs molecular pattern conversion towards a more aggressive triple negative type. PDOs incubation with 0.5-60.0 µM LHT-17-19 was accompanied not only by inhibition of their growth and proliferation, but also by significant cytoreduction. Conclusion: Thus, in two-dimensional and three-dimensional tumor cell cultures, the possibility of controlling the oncogenic expression of EGFR with the acridone compound 9-ammonium-3,3-dimethyl-3,4-dihydroacridine-1(2H)-OH L-2-hydroxybutanedivacate (LHT-17-19) was shown.